A Socio-cultural Portrait of Impersonality: «the Man of the Barracks» - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
As a result of the processes of globalisation taking place in the world, when humanity has entered a force-majeure stage of destruction, when many realities with structural certainty are depersonalised and undermined, man is forced to readjust in the new social environment which he has not yet mastered, to master the opportunities it provides, to try out various social roles, to perceive the transformations and transformations happening to him independently, to measure his social place anew and to project his own life as a result. Undoubtedly, in order not to turn into a "barracks man", the modern man must also make much greater efforts to preserve his individuality, because in the created sociocultural situation he has virtually no unchallenged restrictions or prohibitions, but rather this colourful world constantly provokes and foments new demands, desires and needs.This article analyzes the socio-cultural portrait of the "faceless" and the barracks man in his context, the civilizational processes and transformations that contribute to its formation, as well as several issues concerning its role and impact on social processes.
Keywords: network society; staged society; individualism; globalization; impersonality; barracks man; crowd man; role; mask